Steel and carburized steel parts

A steel material with optimized chemical composition and ratios addresses the challenge of achieving both bending and surface fatigue strength in carburized steel parts, particularly in gears, by controlling carbon penetration and microstructure formation during gas carburizing, resulting in enhanced durability.

JP7606078B2Active Publication Date: 2024-12-25NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020191436
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-18
Publication Date
2024-12-25
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

Existing steel materials used for carburized steel parts do not adequately achieve both bending fatigue strength and surface fatigue strength, particularly in components like gears where tooth surfaces slide against each other, leading to issues such as pitting.

Method used

A steel material with a specific chemical composition ranging from C: 0.10% to 0.35%, Si: 0.45% to 1.00%, Mn: 0.40% to 1.30%, P: 0.030% or less, S: 0.001% to 0.100%, Cr: 1.63% to 2.10%, Al: 0.010% to 0.100%, N: 0.0250% or less, and Mo: 0.02% to 0.60%, with ratios defined by formulas (1) to (3) to optimize the penetration and distribution of carbon during gas carburizing, forming a hardened layer with appropriate microstructure for enhanced strength.

Benefits of technology

The proposed steel material achieves excellent bending fatigue strength and surface fatigue strength in carburized steel parts, effectively suppressing pitting and ensuring high durability in mechanical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606078000003
    Figure 0007606078000003
  • Figure 0007606078000004
    Figure 0007606078000004
  • Figure 0007606078000005
    Figure 0007606078000005
Patent Text Reader

Abstract

To provide a steel that undergoes gas carburization into a carburized steel component, which exhibits excellent bending fatigue strength and surface fatigue strength (pitching properties).SOLUTION: A steel consists of, in mass%, C: 0.10-0.35%, Si: 0.45-1.00%, Mn: 0.40-1.30%, P: 0.030% or less, S: 0.001-0.100%, Cr: 1.63-2.10%, Al: 0.010-0.100%, N: 0.0250% or less, and Mo: 0.02-0.60%, with the balance being Fe and impurities, satisfying formula (1)-formula (3). 6.1≤(Mn+3Cr+2Mo) / Si≤12.0 (1), 3.0≤Cr / Mn (2), 24≤Mn / S≤60 (3), where, each element symbol in the formula (1)-formula (3) is substituted for by the content of a corresponding element in mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a steel material suitable for use as a material for carburized steel parts, and to carburized steel parts. [Background technology]

[0002] In recent years, with the increase in output and miniaturization of power units such as engines and motors, excellent bending fatigue strength is required for power units and mechanical parts used around the power units. Among these mechanical parts, gears used in automobiles, construction vehicles, etc. have tooth surfaces that slide against each other at short intervals. Therefore, pitting must be suppressed on the tooth surfaces. In other words, mechanical parts such as gears used in automobiles, construction vehicles, etc. are required to have not only bending fatigue strength but also surface fatigue strength (pitting characteristics).

[0003] Gas carburizing is known as a method for increasing the bending fatigue strength and surface fatigue strength of mechanical parts. In this specification, gas carburizing includes not only gas carburizing but also gas carbonitriding. In gas carburizing, a hardened layer (carburized layer or carbonitriding layer) is formed on the surface of the mechanical part. It is known that this hardened layer increases the bending fatigue strength and surface fatigue strength of the mechanical part. Therefore, it is required that the steel material that is the raw material for carburized steel parts can have higher bending fatigue strength and surface fatigue strength when the mechanical part (carburized steel part) is made by performing gas carburizing.

[0004] Steel materials that can increase bending fatigue strength and surface fatigue strength when subjected to gas carburizing treatment to form carburized steel parts are proposed in JP 2010-185123 A (Patent Document 1) and JP 2017-214642 A (Patent Document 2).

[0005] The steel material disclosed in Patent Document 1 contains, by mass%, C: 0.15 to 0.25%, Si: 0.40 to 0.80%, Mn: 0.20 to 1.0%, P: 0.030% or less, S: 0.10% or less, Cu: 0.30% or less, Ni: 0.30% or less, Cr: 0.8 to 1.8%, Mo: 0.60% or less, Al: 0.02 to 0.10%, N: 0.005 to 0.03%, O: 0.003% or less, with the balance being Fe and unavoidable impurities, and satisfies the following formulas (1) and (2). 1.8≦2×[Si]+[Cr]≦3.5 (1) 114×[Si]+2×[Cr]+68×[Mo]≧50 (2)

[0006] The steel material disclosed in Patent Document 2 contains, by mass%, C: 0.15 to 0.30%, Si: 0.80% to 2.00%, Mn: 0.20 to 0.80%, P: 0.003 to 0.030%, S: 0.005 to 0.050%, Cr: 1.00 to less than 1.80%, Mo: 0.03 to 0.30%, Al: 0.020 to 0.060%, N: 0.0060 to 0.0300%, and O: 0.0003 to 0.0025%, with the balance being Fe and unavoidable impurities, and satisfies the following formulas (1) to (3). [%Si]+([%Mn]+[%Cr]+[%Mo]) / 3≧1.5 (1) 180-45[%Mn]-14[%Cr]-51[%Mo]+5[%Si]≧125 (2) √I≦80 (3) Here, I is the area (μm2) of oxide inclusions located at the center of fisheyes on the fracture surface after the steel material is carburized, quenched, and tempered, and then subjected to a rotating bending fatigue test. 2 ) is shown. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2010-185123 A [Patent Document 2] JP 2017-214642 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, excellent bending fatigue strength and excellent surface fatigue strength may be obtained when a carburized steel part is produced by carrying out gas carburizing treatment using a means different from that proposed in Patent Documents 1 and 2.

[0009] An object of the present disclosure is to provide a steel material and a carburized steel part that, when subjected to gas carburizing treatment to form a carburized steel part, exhibit excellent bending fatigue strength and excellent surface fatigue strength (pitting characteristics). [Means for solving the problem]

[0010] The steel material according to the present disclosure is Chemical composition in mass percent: C: 0.10-0.35%, Si: 0.45 to 1.00%, Mn: 0.40-1.30%, P:0.030% or less, S: 0.001~0.100%, Cr: 1.63-2.10%, Al: 0.010 to 0.100%, N: 0.0250% or less, and Mo: 0.02-0.60%, and the balance being Fe and impurities, and satisfying formulas (1) to (3). 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1) 3.0≦Cr / Mn (2) 24.0≦Mn / S≦60.0 (3) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (3).

[0011] The carburized steel component according to the present disclosure comprises: A hardened layer; A core portion is provided inside the hardened layer, The chemical composition of the core is, in mass%, C: 0.10-0.35%, Si: 0.45 to 1.00%, Mn: 0.40-1.30%, P: 0.030% or less, S: 0.001~0.100%, Cr: 1.63-2.10%, Al: 0.010 to 0.100%, N: 0.0250% or less, and Mo: 0.02 to 0.60%, and the balance being Fe and impurities, and satisfying formulas (1) to (3), The carbon concentration in a region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more by mass%, The microstructure of the carburized steel part at a depth of 20 μm from the surface is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1) 3.0≦Cr / Mn (2) 24.0≦Mn / S≦60.0 (3) Effect of the Invention

[0012] When the steel material according to the present disclosure is subjected to gas carburizing treatment to form a carburized steel part, excellent bending fatigue strength and excellent surface fatigue strength (pitting properties) can be obtained. The carburized steel part according to the present disclosure has excellent bending fatigue strength and excellent surface fatigue strength. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a diagram showing an example of a heat pattern in a gas carburizing treatment (a gas carburizing step and a quenching step). [Diagram 2] FIG. 2 is a side view of a small roller test piece prepared in the example. [Diagram 3] FIG. 3 is a side view of a rotating bending fatigue test piece prepared in the example. [Figure 4]FIG. 4 is a front view of a large roller test piece prepared in the example. [Diagram 5] FIG. 5 is a schematic diagram of a twin roller rolling fatigue test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present inventors have conducted research into steel materials that can provide excellent bending fatigue strength and excellent surface fatigue strength (pitting properties) when they are made into carburized steel parts by gas carburizing (gas carburizing or gas carbonitriding). For such steel materials, gas carburizing is performed, for example, as described above, in the manufacturing process of the carburized steel parts. In gas carburizing, the steel material is subjected to A c3 Since the steel is heated to above its transformation temperature, the microstructure of the steel is transformed into austenite, and the influence of the previous structure is eliminated. Therefore, the inventors of the present invention have investigated ways to increase the bending fatigue strength and surface fatigue strength of carburized steel parts not from the viewpoint of the microstructure of the steel, but from the viewpoint of the chemical composition that remains unchanged even when gas carburizing is performed. As a result, the inventors of the present invention have concluded that it is effective to increase the contents of Si, Cr, Mn, and Mo, which increase temper softening resistance, in order to increase the surface fatigue strength (pitting characteristics). Then, the compatibility of bending fatigue strength and surface fatigue strength was examined from the viewpoint of chemical composition, and the results were as follows, in mass%, C: 0.10-0.35%, Si: 0.45-1.00%, Mn: 0.40-1.30%, P: 0.030% or less, S: 0.001-0.100%, Cr: 1.63-2.10%, Al: 0.010-0.100%, N: 0.0250% or less, Mo: 0.02-0.60%, V: 0-0.50%, Nb: 0-0.100%, Ti: 0-0.200%, Cu: 0-0.50%, Ni: 0- It was considered that if a steel material having a chemical composition consisting of Fe:0.30%, W:0-0.50%, Co:0-0.50%, B:0-0.0050%, Ca:0-0.0014%, Mg:0-0.010%, rare earth elements:0-0.0100%, Te:0-0.100%, Bi:0-0.500%, Pb:0-0.09%, Sn:0-0.014%, and Sb:0-0.0018%, would be able to obtain excellent bending fatigue strength and excellent surface fatigue strength when a carburized steel part is manufactured by carrying out a gas carburizing treatment.

[0015] However, even when the contents of the elements in the chemical composition of a steel material are within the above-mentioned ranges, there are cases in which sufficient bending fatigue strength and surface fatigue strength are not obtained when the steel material is gas carburized to produce a carburized steel part. Therefore, the present inventors have further investigated and studied the matter. As a result, the present inventors have come to the following findings.

[0016] (A) Si, Cr, Mn and Mo are all elements that increase the temper softening resistance of steel and increase surface fatigue strength (pitting characteristics). Here, Mn, Cr and Mo lower the chemical potential of carbon (C) in the steel surface layer in the temperature range where gas carburizing is performed. On the other hand, Si increases the chemical potential of C in the steel surface layer in the temperature range where gas carburizing is performed.

[0017] The higher the chemical potential of C in the steel surface layer in the temperature range where gas carburizing is performed, the more difficult it is for C in the atmosphere to penetrate into the steel surface layer. Although Si, Cr, Mn, and Mo are all elements that increase temper softening resistance, if the Si content is too high relative to the Mn, Cr, and Mo contents, the chemical potential of C in the steel surface layer becomes too high in the temperature range where gas carburizing is performed, making it difficult for C to penetrate into the steel. As a result, the surface fatigue strength of the carburized steel part is reduced rather than increased. On the other hand, if the Mn, Cr, and Mo contents are too high relative to the Si content, the chemical potential of carbon (C) in the steel surface layer becomes too low in the temperature range where gas carburizing is performed, causing excessive C to penetrate into the steel. In this case, a large amount of cementite is generated in the steel. Cementite becomes the starting point of cracks in bending fatigue, so the bending fatigue strength of the carburized steel part is reduced rather than increased.

[0018] By setting the ratio of the Mn, Cr and Mo contents to the Si content in an appropriate range, the chemical potential of C in the steel surface layer will be in an appropriate range in the temperature range in which gas carburizing is performed, and the C concentration penetrating into the steel will be in an appropriate range. As a result, a hardened layer with a sufficient C concentration can be formed in the surface layer of the carburized steel part while suppressing the formation of cementite. As a result, the bending fatigue strength and surface fatigue strength of the carburized steel part can be increased.

[0019] It is defined as F1=(Mn+3Cr+2Mo) / Si. If F1 is 6.1-12.0, that is, if the following formula (1) is satisfied, the Si content relative to the Mn, Cr, and Mo contents is in an appropriate range, and therefore the chemical potential of C during gas carburizing is in an appropriate range. Therefore, an appropriate amount of C penetrates and diffuses into the steel material during gas carburizing. As a result, carburized steel parts manufactured using the steel material as a material can obtain excellent bending fatigue strength and excellent surface fatigue strength, provided that the content of each element in the chemical composition is within the above-mentioned range and satisfies the formulas (2) and (3) described below. 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1)

[0020] (B) When the content of each element in the chemical composition is within the above-mentioned range, both Cr and Mn form a Cr oxide layer and a Mn oxide layer on the surface layer of the steel material during gas carburizing treatment. The Mn oxide layer is more likely to form deeper in the steel material than the Cr oxide layer. Therefore, in bending fatigue, the Mn oxide layer is more likely to be the starting point of cracks than the Cr oxide layer. Therefore, if the formation of the Mn oxide layer can be suppressed, the bending fatigue strength of the carburized steel part can be increased. If the ratio of the Cr content to the Mn content is increased, the Cr oxide layer is more likely to form than the Mn oxide layer during gas carburizing treatment. As a result, the formation of the Mn oxide layer can be suppressed.

[0021] F2 is defined as F2=Cr / Mn. If F2 is 3.0 or more, that is, if the following formula (2) is satisfied, the formation of a Mn oxide layer can be effectively suppressed. As a result, excellent bending fatigue strength can be obtained in carburized steel parts manufactured using steel material, provided that the content of each element in the chemical composition is within the above-mentioned range and formula (1) and formula (3) described below are satisfied. 3.0≦Cr / Mn (2)

[0022] (C) When the content of each element in the chemical composition is within the above-mentioned range, Mn combines with S to form MnS. MnS improves the machinability of steel. However, coarse MnS can be the starting point of cracks during bending fatigue of carburized steel parts. Therefore, if a large amount of coarse MnS is formed, the bending fatigue strength of the carburized steel part decreases. Therefore, if the ratio of Mn content to S content can be appropriately adjusted to suppress the formation of coarse MnS, the bending fatigue strength of the carburized steel part can be increased.

[0023] F3 is defined as Mn / S. If F3 is 24.0 to 60.0, the formation of coarse MnS can be effectively suppressed. As a result, sufficient bending fatigue strength can be obtained in a carburized steel part manufactured using the steel material, provided that the content of each element in the chemical composition is within the above-mentioned range and formulas (1) and (2) are satisfied.

[0024] The steel material of this embodiment has been completed based on the above technical concept, and has the following configuration.

[0025] [1] Chemical composition in mass percent: C: 0.10-0.35%, Si: 0.45 to 1.00%, Mn: 0.40-1.30%, P:0.030% or less, S: 0.001~0.100%, Cr: 1.63-2.10%, Al: 0.010 to 0.100%, N: 0.0250% or less, and Mo: 0.02 to 0.60%, and the balance being Fe and impurities, and satisfying formulas (1) to (3). Steel material. 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1) 3.0≦Cr / Mn (2) 24.0≦Mn / S≦60.0 (3) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (3).

[0026] [2] The steel material according to [1], The chemical composition is such that, in place of a portion of Fe, V: 0.50% or less, Nb: 0.100% or less, Ti: 0.200% or less, Cu: 0.50% or less, Ni: 0.30% or less, W: 0.50% or less, Co: 0.50% or less, and B: 0.0050% or less, Contains one or more selected from the group consisting of Steel material.

[0027] [3] The steel material according to [1] or [2], The chemical composition is such that, in place of a portion of Fe, Ca: 0.0014% or less, Mg: 0.010% or less, and Rare earth elements: 0.0100% or less, Contains one or more selected from the group consisting of Steel material.

[0028] [4] The steel material according to any one of [1] to [3], The chemical composition is such that, in place of a portion of Fe, Te: 0.100% or less, Bi: 0.500% or less, Pb: 0.09% or less, Sn: 0.014% or less, and Sb: 0.0018% or less, Contains one or more selected from the group consisting of Steel material.

[0029] [5] A carburized steel part, A hardened layer; A core portion is provided inside the hardened layer, The chemical composition of the core is, in mass%, C: 0.10-0.35%, Si: 0.45 to 1.00%, Mn: 0.40-1.30%, P:0.030% or less, S: 0.001~0.100%, Cr: 1.63-2.10%, Al: 0.010 to 0.100%, N: 0.0250% or less, and Mo: 0.02-0.60%, and the balance being Fe and impurities, and satisfying formulas (1) to (3), The carbon concentration in a region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more by mass%, The microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. Carburized steel parts. 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1) 3.0≦Cr / Mn (2) 24.0≦Mn / S≦60.0 (3)

[0030] [6] A carburized steel part according to [5], The chemical composition of the core portion is, in place of a part of Fe, V: 0.50% or less, Nb: 0.100% or less, Ti: 0.200% or less, Cu: 0.50% or less, Ni: 0.30% or less, W: 0.50% or less, Co: 0.50% or less, and B: 0.0050% or less, Contains one or more selected from the group consisting of Carburized steel parts.

[0031] [7] A carburized steel part according to [5] or [6], The chemical composition of the core portion is, in place of a part of Fe, Ca: 0.0014% or less, Mg: 0.010% or less, and Rare earth elements: 0.0100% or less, Contains one or more selected from the group consisting of Carburized steel parts.

[0032] [8] A carburized steel part according to any one of [5] to [7], The chemical composition of the core portion is, in place of a part of Fe, Te: 0.100% or less, Bi: 0.500% or less, Pb: 0.09% or less, Sn: 0.014% or less, and Sb: 0.0018% or less, Contains one or more selected from the group consisting of Carburized steel parts.

[0033] The steel material according to this embodiment and the carburized steel part manufactured using this steel material as a raw material will be described in detail below. The "%" for the content of each element means "mass %" unless otherwise specified.

[0034] [Steel use] The steel material of this embodiment is suitable as a material for carburized steel parts. Specifically, the steel material of this embodiment is suitable as a material for carburized steel parts manufactured by carrying out a gas carburizing process. In this specification, the gas carburizing process also includes a gas carbonitriding process.

[0035] [Chemical composition of steel] The chemical composition of the steel material of this embodiment contains the following elements.

[0036] C: 0.10-0.35% Carbon (C) improves the hardenability of steel and increases the hardness of the core of carburized steel parts manufactured using the steel material. Therefore, it increases the bending fatigue strength of the carburized steel parts. If the C content is less than 0.10%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the C content exceeds 0.35%, the machinability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the C content is 0.10 to 0.35%. The preferred lower limit of the C content is 0.11%, more preferably 0.12%, and even more preferably 0.13%. The preferred upper limit of the C content is 0.32%, more preferably 0.30%, and even more preferably 0.28%.

[0037] Silicon: 0.45 to 1.00% Silicon (Si) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting properties) of carburized steel parts manufactured using the steel as a raw material. If the Si content is less than 0.45%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Si content exceeds 1.00%, the chemical potential of C in the steel surface layer in the temperature range of the gas carburizing treatment is excessively increased even if the contents of other elements are within the range of this embodiment. In this case, the penetration of C into the steel during the gas carburizing treatment is suppressed. Therefore, the depth of the surface layer (hardened layer) of the carburized steel part decreases, and the surface fatigue strength decreases. Therefore, the Si content is 0.45 to 1.00%. The preferable lower limit of the Si content is 0.50%, more preferably 0.55%, and more preferably 0.60%. The preferable upper limit of the Si content is 0.95%, more preferably 0.92%, and more preferably 0.90%.

[0038] Mn: 0.40-1.30% Manganese (Mn) improves the hardenability of steel and increases the hardness of the core of a carburized steel part manufactured using the steel as a material. Therefore, it increases the bending fatigue strength of the carburized steel part. Mn also increases the temper softening resistance of steel, and as a result, it increases the surface fatigue strength (pitting characteristics) of a carburized steel part manufactured using the steel as a material. If the Mn content is less than 0.40%, the above effects cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mn content exceeds 1.30%, the chemical potential of C in the steel surface layer in the temperature range of the gas carburizing treatment is excessively reduced, and C penetrates and diffuses excessively into the steel during the gas carburizing treatment. Therefore, cementite is excessively formed in the carburized steel part. As a result, the bending fatigue strength of the carburized steel part is reduced. Therefore, the Mn content is 0.40 to 1.30%. The preferable lower limit of the Mn content is 0.41%, more preferably 0.42%, and even more preferably 0.43%. The upper limit of the Mn content is preferably 1.00%, more preferably 0.80%, more preferably 0.70%, more preferably 0.68%, more preferably 0.65%, and more preferably 0.62%.

[0039] P:0.030% or less Phosphorus (P) is an impurity. In the gas carburizing process when manufacturing a carburized steel part using a steel material as a base material, P segregates at the austenite grain boundary, lowering the bending fatigue strength of the carburized steel part. If the P content exceeds 0.030%, the bending fatigue strength of the carburized steel part is significantly lowered even if the contents of other elements are within the range of this embodiment. Therefore, the P content is 0.030% or less. The preferred upper limit of the P content is 0.029%, more preferably 0.028%, and even more preferably 0.025%. The P content is preferably as low as possible. However, excessive reduction of the P content increases the manufacturing cost. Therefore, in consideration of normal industrial production, the preferred lower limit of the P content is 0.001%, and even more preferably 0.002%.

[0040] S: 0.001 to 0.100% Sulfur (S) combines with Mn to form MnS, improving the machinability of steel. If the S content is less than 0.001%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the S content exceeds 0.100%, the sulfides become coarse even if the contents of other elements are within the range of this embodiment. In this case, the bending fatigue strength of the carburized steel part decreases. Therefore, the S content is 0.001 to 0.100%. The preferred lower limit of the S content is 0.002%, more preferably 0.005%, and even more preferably 0.007%. The preferred upper limit of the S content is 0.090%, more preferably 0.080%, more preferably 0.070%, and even more preferably 0.060%.

[0041] Cr: 1.63~2.10% Chromium (Cr) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting properties) of carburized steel parts manufactured using the steel as a raw material. If the Cr content is less than 1.63%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Cr content exceeds 2.10%, even if the contents of other elements are within the range of this embodiment, the chemical potential of C in the steel surface layer in the temperature range of the gas carburizing treatment is excessively reduced, and C penetrates and diffuses excessively into the steel during the gas carburizing treatment. Therefore, cementite is excessively formed in the carburized steel part. As a result, the bending fatigue strength of the carburized steel part is reduced. Therefore, the Cr content is 1.63 to 2.10%. The preferable lower limit of the Cr content is 1.64%, more preferably 1.65%, more preferably 1.68%, more preferably 1.70%, and more preferably 1.75%. The upper limit of the Cr content is preferably 2.05%, more preferably 2.04%, still more preferably 2.03%, still more preferably 2.02%, and still more preferably 2.00%.

[0042] Al: 0.010 to 0.100% Aluminum (Al) deoxidizes steel. If the Al content is less than 0.010%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Al content exceeds 0.100%, coarse oxide-based inclusions are generated even if the contents of other elements are within the range of this embodiment. The coarse oxide-based inclusions reduce the bending fatigue strength of the carburized steel part. Therefore, the Al content is 0.010 to 0.100%. The preferred lower limit of the Al content is 0.013%, more preferably 0.015%, and even more preferably 0.018%. The preferred upper limit of the Al content is 0.090%, more preferably 0.080%, and even more preferably 0.070%.

[0043] N: 0.0250% or less Nitrogen (N) is an impurity. If the N content exceeds 0.0250%, coarse nitrides will be generated even if the contents of other elements are within the range of this embodiment. The coarse nitrides reduce the bending fatigue strength of the carburized steel parts. Therefore, the N content is 0.0250% or less. The preferred upper limit of the N content is 0.0230%, more preferably 0.0210%, and even more preferably 0.0200%. The N content is preferably as low as possible. However, if the N content is reduced excessively, the manufacturing cost will increase. Therefore, in consideration of normal industrial production, the preferred lower limit of the N content is 0.0001%, and even more preferably 0.0005%.

[0044] Mo: 0.02 to 0.60% Molybdenum (Mo) increases the temper softening resistance of steel, and as a result, increases the surface fatigue strength (pitting properties) of carburized steel parts manufactured using the steel as a raw material. If the Mo content is less than 0.02%, the above effect cannot be sufficiently obtained even if the contents of other elements are within the range of this embodiment. On the other hand, if the Mo content exceeds 0.60%, even if the contents of other elements are within the range of this embodiment, the chemical potential of C in the steel surface layer in the temperature range of the gas carburizing treatment is excessively reduced, and C penetrates and diffuses excessively into the steel during the gas carburizing treatment. Therefore, cementite is excessively formed in the carburized steel part. As a result, the bending fatigue strength of the carburized steel part is reduced. Therefore, the Mo content is 0.02 to 0.60%. The preferred lower limit of the Mo content is 0.03%, more preferably 0.04%, and more preferably 0.05%. The preferred upper limit of the Mo content is 0.55%, more preferably 0.50%, and more preferably 0.45%.

[0045] The balance of the chemical composition of the steel material according to the present embodiment is composed of Fe and impurities. Here, the term "impurities" refers to substances that are mixed in from raw materials such as ore and scrap, or from the manufacturing environment, during industrial production of the steel material, and are permissible within a range that does not adversely affect the steel material according to the present embodiment.

[0046] [Optional elements] The steel material of this embodiment may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of V, Nb, Ti, Cu, Ni, W, Co, and B. Any of these elements increases the bending fatigue strength of a carburized steel part manufactured using the steel material as a material.

[0047] V: 0.50% or less Vanadium (V) is an optional element and may not be contained. In other words, the V content may be 0%. When vanadium is contained, that is, when the V content is more than 0%, V forms precipitates (carbides, nitrides, carbonitrides, etc.) and suppresses the coarsening of crystal grains of the steel material during gas carburization treatment due to the pinning effect. As a result, the bending fatigue strength of the carburized steel part manufactured using the steel material as a raw material is increased. If even a small amount of V is contained, the above effect can be obtained to a certain extent. However, if the V content exceeds 0.50%, the hardness of the steel material becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel material decreases. Therefore, the V content is 0 to 0.50%, and when contained, it is 0.50% or less. The preferable lower limit of the V content is 0.01%, more preferably 0.05%, and more preferably 0.10%. The preferable upper limit of the V content is 0.40%, and more preferably 0.30%.

[0048] Nb: 0.100% or less Niobium (Nb) is an optional element and may not be contained. In other words, the Nb content may be 0%. When it is contained, that is, when the Nb content is more than 0%, Nb forms precipitates (carbides, carbonitrides, etc.) and suppresses the coarsening of crystal grains of steel during gas carburization treatment by the pinning effect. As a result, the bending fatigue strength of carburized steel parts manufactured using the steel as a raw material is increased. If even a small amount of Nb is contained, the above effect can be obtained to some extent. However, if the Nb content exceeds 0.100%, even if the contents of other elements are within the range of this embodiment, the Nb precipitates become coarse and the pinning effect cannot be obtained. Therefore, the Nb content is 0 to 0.100%, and when it is contained, it is 0.100% or less. The preferable lower limit of the Nb content is 0.001%, and more preferably 0.005%. The upper limit of the Nb content is preferably 0.060%, more preferably 0.050%, further preferably 0.040%, and further preferably 0.030%.

[0049] Ti: 0.200% or less Titanium (Ti) is an optional element and may not be contained. In other words, the Ti content may be 0%. When titanium is contained, that is, when the Ti content is more than 0%, Ti forms precipitates (carbides, nitrides, carbonitrides, etc.) and suppresses the coarsening of crystal grains of steel during gas carburization treatment due to the pinning effect. As a result, the bending fatigue strength of carburized steel parts manufactured using steel as a raw material is increased. If even a small amount of Ti is contained, the above effect can be obtained to a certain extent. However, if the Ti content exceeds 0.200%, even if the contents of other elements are within the range of this embodiment, the Ti precipitates become coarse and the pinning effect cannot be obtained. Therefore, the Ti content is 0 to 0.200%, and if contained, it is 0.200% or less. The preferable lower limit of the Ti content is 0.001%, more preferably 0.005%, and more preferably 0.010%. The preferable upper limit of the Ti content is 0.150%, and more preferably 0.120%.

[0050] Cu: 0.50% or less Copper (Cu) is an optional element and may not be contained. In other words, the Cu content may be 0%. When copper is contained, that is, when the Cu content is more than 0%, Cu enhances the hardenability of the steel and enhances the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Cu is contained, the above effect can be obtained to a certain extent. On the other hand, if the Cu content exceeds 0.50%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Cu content is 0 to 0.50%, and if contained, it is 0.50% or less. The preferred lower limit of the Cu content is 0.01%, more preferably 0.05%, more preferably 0.08%, and more preferably 0.10%. The preferred upper limit of the Cu content is 0.48%, and more preferably 0.46%.

[0051] Ni: 0.30% or less Nickel (Ni) is an optional element and may not be contained. In other words, the Ni content may be 0%. When nickel is contained, that is, when the Ni content is more than 0%, Ni increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Ni is contained, the above effect can be obtained to a certain extent. However, if the Ni content exceeds 0.30%, the strength of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel decreases. Therefore, the Ni content is 0 to 0.30%, and if contained, it is 0.30% or less. The preferred lower limit of the Ni content is 0.01%, more preferably 0.05%, and more preferably 0.10%. The preferred upper limit of the Ni content is 0.29%, more preferably 0.28%, and more preferably 0.27%.

[0052] W: 0.50% or less Tungsten (W) is an optional element and may not be contained. That is, the W content may be 0%. When it is contained, that is, when the W content is more than 0%, W increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of W is contained, the above effect can be obtained to a certain extent. On the other hand, if the W content exceeds 0.50%, the strength of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel decreases. Therefore, the W content is 0 to 0.50%, and when it is contained, it is 0.50% or less. The preferable lower limit of the W content is 0.01%, more preferably 0.05%, and more preferably 0.08%. The preferable upper limit of the W content is 0.40%, and more preferably 0.30%.

[0053] Co:0.50% or less Cobalt (Co) is an optional element and may not be contained. In other words, the Co content may be 0%. When it is contained, that is, when the Co content is more than 0%, Co increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Co is contained, the above effect can be obtained to a certain extent. On the other hand, if the Co content exceeds 0.50%, the strength of the steel becomes excessively high even if the contents of other elements are within the range of this embodiment. In this case, the machinability of the steel decreases. Therefore, the Co content is 0 to 0.50%, and when it is contained, it is 0.50% or less. The preferred lower limit of the Co content is 0.01%, more preferably 0.05%, and more preferably 0.08%. The preferred upper limit of the Co content is 0.40%, and more preferably 0.30%.

[0054] B: 0.0050% or less Boron (B) is an optional element and may not be contained. In other words, the B content may be 0%. When it is contained, that is, when the B content is more than 0%, B increases the hardenability of the steel and increases the hardness of the core of the carburized steel part manufactured using the steel material as a material. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of B is contained, the above effect can be obtained to a certain extent. On the other hand, if the B content exceeds 0.0050%, the effect is saturated. Therefore, the B content is 0 to 0.0050%, and if contained, it is 0.0050% or less. The preferred lower limit of the B content is 0.0001%, more preferably 0.0002%, and more preferably 0.0003%. The preferred upper limit of the B content is 0.0045%, more preferably 0.0040%, more preferably 0.0030%, more preferably 0.0020%, and more preferably 0.0015%.

[0055] The steel material of this embodiment may further contain one or more elements selected from the group consisting of Ca, Mg, and rare earth elements (REM) in place of a portion of Fe. These elements are optional elements, and all of them increase the bending fatigue strength of the carburized steel part.

[0056] Ca:0.0014% or less Calcium (Ca) is an optional element and may not be contained. In other words, the Ca content may be 0%. When it is contained, that is, when the Ca content is more than 0%, Ca modifies the sulfides in the steel material and inhibits the sulfides from elongating during hot working. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Ca is contained, the above effect can be obtained to a certain extent. However, if the Ca content exceeds 0.0014%, the above effect is saturated. Therefore, the Ca content is 0 to 0.0014%, and if contained, it is 0.0014% or less. The preferable lower limit of the Ca content is 0.0001%, and more preferably 0.0002%. The preferable upper limit of the Ca content is 0.0012%, and more preferably 0.0010%.

[0057] Mg: 0.010% or less Magnesium (Mg) is an optional element and may not be contained. That is, the Mg content may be 0%. When magnesium is contained, that is, when the Mg content is more than 0%, Mg modifies sulfides in the steel material and inhibits the sulfides from elongating during hot working. As a result, the bending fatigue strength of the carburized steel part is increased. If even a small amount of Mg is contained, the above effect can be obtained to a certain extent. However, if the Mg content exceeds 0.010%, the above effect is saturated. Therefore, the Mg content is 0 to 0.010%, and if contained, it is 0.010% or less. The preferable lower limit of the Mg content is 0.001%, and more preferably 0.002%. The preferable upper limit of the Mg content is 0.009%, and more preferably 0.008%.

[0058] Rare earth elements: 0.0100% or less Rare earth elements (REM) are optional elements and may not be contained. That is, the REM content may be 0%. When contained, that is, when the REM content is more than 0%, REM modifies sulfides in the steel material and inhibits the sulfides from elongating during hot working. As a result, the bending fatigue strength of the carburized steel part is increased. Even if even a small amount of REM is contained, the above effect can be obtained to some extent. However, if the REM content exceeds 0.0100%, the formation of coarse oxides is promoted even if the contents of other elements are within the range of this embodiment. In this case, the bending fatigue strength of the carburized steel part is reduced. Therefore, the REM content is 0 to 0.0100%, and when contained, it is 0.0100% or less. The preferable lower limit of the REM content is 0.0001%, more preferably 0.0010%, and more preferably 0.0020%. The preferable upper limit of the REM content is 0.0098%, and more preferably 0.0097%.

[0059] The steel material of the present embodiment may further contain one or more elements selected from the group consisting of Te, Bi, Pb, Sn, and Sb in place of a portion of Fe. These elements are optional elements, and all of them improve the machinability of the steel material.

[0060] Te: 0.100% or less Tellurium (Te) is an optional element and may not be contained. That is, the Te content may be 0%. When it is contained, that is, when the Te content is more than 0%, Te enhances the machinability of the steel material. If even a small amount of Te is contained, the above effect can be obtained to some extent. However, if the Te content exceeds 0.100%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Te content is 0 to 0.100%, and when it is contained, it is 0.100% or less. The preferred lower limit of the Te content is 0.001%, and more preferably 0.002%. The preferred upper limit of the Te content is 0.095%, and more preferably 0.090%.

[0061] Bi:0.500% or less Bismuth (Bi) is an optional element and may not be contained. That is, the Bi content may be 0%. When contained, that is, when the Bi content is more than 0%, Bi enhances the machinability of the steel. If even a small amount of Bi is contained, the above effect can be obtained to some extent. However, if the Bi content exceeds 0.500%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Bi content is 0 to 0.500%, and if contained, it is 0.500% or less. The preferred lower limit of the Bi content is 0.001%, more preferably 0.005%, and more preferably 0.010%. The preferred upper limit of the Bi content is 0.400%, more preferably 0.300%, more preferably 0.200%, more preferably 0.100%, more preferably 0.080%, and more preferably 0.070%.

[0062] Pb: 0.09% or less Lead (Pb) is an optional element and may not be contained. That is, the Pb content may be 0%. When it is contained, that is, when the Pb content is more than 0%, Pb enhances the machinability of the steel material. If even a small amount of Pb is contained, the above effect can be obtained to some extent. However, if the Pb content exceeds 0.09%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Pb content is 0 to 0.09%, and if it is contained, it is 0.09% or less. The preferable lower limit of the Pb content is 0.01%, and more preferably 0.02%. The preferable upper limit of the Pb content is 0.08%, and more preferably 0.07%.

[0063] Sn: 0.014% or less Tin (Sn) is an optional element and may not be contained. In other words, the Sn content may be 0%. When it is contained, that is, when the Sn content is more than 0%, Sn enhances the machinability of the steel material. If even a small amount of Sn is contained, the above effect can be obtained to some extent. However, if the Sn content exceeds 0.014%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Sn content is 0 to 0.014%, and when it is contained, it is 0.014% or less. The preferable lower limit of the Sn content is 0.001%, and more preferably 0.005%. The preferable upper limit of the Sn content is 0.013%, and more preferably 0.010%.

[0064] Sb: 0.0018% or less Antimony (Sb) is an optional element and may not be contained. In other words, the Sb content may be 0%. When it is contained, that is, when the Sb content is more than 0%, Sb enhances the machinability of the steel material. If even a small amount of Sb is contained, the above effect can be obtained to some extent. However, if the Sb content exceeds 0.0018%, the hot workability of the steel material decreases even if the contents of other elements are within the range of this embodiment. Therefore, the Sb content is 0 to 0.0018%, and if it is contained, it is 0.0018% or less. The preferable lower limit of the Sb content is 0.0001%, and more preferably 0.0005%. The preferable upper limit of the Sb content is 0.0017%, and more preferably 0.0016%.

[0065] [Regarding formulas (1) to (3)] The chemical composition of the steel material of this embodiment further satisfies formulas (1) to (3), on the premise that the content of each element is within the range of this embodiment described above. 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1) 3.0≦Cr / Mn (2) 24.0≦Mn / S≦60.0 (3) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (3). Each formula will be explained below.

[0066] [Regarding formula (1)] It is defined as F1=(Mn+3Cr+2Mo) / Si. F1 is an index showing the ease of penetration of carbon (C) into steel in gas carburizing treatment during the manufacturing process of manufacturing carburized steel parts using steel as a raw material. In the chemical composition of the steel of this embodiment, Mn, Cr and Mo all lower the chemical potential of C in the temperature range of gas carburizing treatment, making it easier for C to penetrate into the steel. On the other hand, Si increases the chemical potential of C in the temperature range of gas carburizing treatment, making it harder for C to penetrate into the steel. Therefore, in the chemical composition of the steel of this embodiment, the amount of C that penetrates into the steel in gas carburizing treatment can be adjusted by appropriately adjusting the contents of Mn, Cr, Mo and Si, assuming that the contents of each element are within the range of this embodiment.

[0067] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, when F1 is less than 6.1, the Si content is excessively high compared to the contents of Mn, Cr, and Mo. In this case, the chemical potential of C becomes excessively high during gas carburizing treatment. Therefore, the amount of C penetrating into the steel material during gas carburizing treatment becomes insufficient. As a result, the hardness of the surface layer of the carburized steel part decreases, and the surface fatigue strength (pitting characteristics) decreases.

[0068] On the other hand, in the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, when F1 exceeds 12.0, the contents of Mn, Cr, and Mo are high relative to the Si content. In this case, the chemical potential of C becomes excessively low during gas carburizing treatment. In this case, the amount of C penetrating into the steel material during gas carburizing treatment becomes excessively large. As a result, cementite is generated in the steel material. Cementite is likely to become the starting point of crack generation. Therefore, the bending fatigue strength of the carburized steel part decreases.

[0069] If F1 is 6.1 to 12.0, the Si content relative to the Mn, Cr, and Mo contents is in an appropriate range, and therefore the chemical potential of C during gas carburizing is in an appropriate range. Therefore, an appropriate amount of C penetrates and diffuses into the steel material during gas carburizing. As a result, carburized steel parts manufactured using the steel material have high bending fatigue strength and high surface fatigue strength.

[0070] The preferred lower limit of F1 is 6.2, more preferably 6.4, and more preferably 6.5. The preferred upper limit of F1 is 11.9, more preferably 11.8, more preferably 11.5, more preferably 11.0, more preferably 10.5, more preferably 10.0, more preferably 9.5, and more preferably 9.0. F1 is a value obtained by rounding off the first decimal place of the value obtained by calculation.

[0071] [Regarding formula (2)] F2 is defined as F2=Cr / Mn. F2 is an index related to the oxide layer that affects bending fatigue strength. Both Cr and Mn form Cr oxide layer and Mn oxide layer on the surface of steel during gas carburizing treatment. Mn oxide layer is more likely to form deeper in steel than Cr oxide layer. Therefore, Mn oxide layer is more likely to be the starting point of cracks than Cr oxide layer during bending fatigue, and reduces bending fatigue strength of carburized steel parts. On the other hand, if the Cr content is high relative to the Mn content, Cr forms the oxide layer in preference to Mn. As mentioned above, Cr oxide layer is formed shallower than Mn oxide layer, so it has less effect on bending fatigue strength.

[0072] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F2 is less than 3.0, the Cr content is too low compared to the Mn content in the steel material. In this case, an excessive Mn oxide layer is formed during gas carburizing treatment. As a result, the bending fatigue strength of the carburized steel part manufactured using the steel material as a material is reduced.

[0073] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F2 is 3.0 or more, the Cr content is high relative to the Mn content in the steel material. Therefore, the formation of a Mn oxide layer can be sufficiently suppressed in the gas carburizing treatment. As a result, the carburized steel part can obtain sufficient bending fatigue strength.

[0074] The lower limit of F2 is preferably 3.1, more preferably 3.2, and even more preferably 3.3. The upper limit of F2 is not particularly limited, but considering the upper limit of the Cr content and the lower limit of the Mn content in the chemical composition of this embodiment, the upper limit of F2 is preferably 10.5. Note that F2 is a value obtained by rounding off the first decimal place of the value obtained by calculation.

[0075] [Regarding formula (3)] It is defined as F3=Mn / S. F3 is an index related to MnS, which affects bending fatigue strength. MnS improves the machinability of steel materials. However, coarse MnS can be the starting point of cracks during bending fatigue of carburized steel parts. Therefore, if a lot of coarse MnS is formed, the bending fatigue strength of the carburized steel parts will decrease.

[0076] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F3 is less than 24.0, the S content is excessively high relative to the Mn content in the steel material. In this case, coarse MnS is formed in excess. As a result, the bending fatigue strength of the carburized steel part manufactured using the steel material as a material is reduced.

[0077] On the other hand, in the chemical composition of the steel material of this embodiment, if F3 exceeds 60.0, assuming that the content of each element is within the range of this embodiment, the Mn content in the steel material is excessively high relative to the S content. In this case, Mn segregates near the central axis of the steel material. Therefore, in this central segregation portion, coarse MnS is excessively formed. As a result, the bending fatigue strength of the carburized steel part manufactured using the steel material as a material is reduced.

[0078] In the chemical composition of the steel material of this embodiment, assuming that the content of each element is within the range of this embodiment, if F3 is 24.0 to 60.0, the relationship between the Mn content and the S content is appropriate. Therefore, it is possible to suppress the excessive generation of coarse MnS. As a result, sufficient bending fatigue strength is obtained in the carburized steel part manufactured using the steel material as a material.

[0079] The preferred lower limit of F3 is 24.5, more preferably 25.0, more preferably 25.5, and more preferably 26.0. The preferred upper limit of F3 is 58.0, more preferably 56.0, more preferably 54.0, more preferably 52.0, more preferably 50.0, more preferably 46.0, and more preferably 44.0. F3 is a value obtained by rounding off the first decimal place of the value obtained by calculation.

[0080] [About the microstructure of steel] The microstructure of the steel material of this embodiment is not particularly limited. The objective of the steel material of this embodiment is to obtain high bending fatigue strength and high surface fatigue strength in a carburized steel part manufactured using the steel material as a raw material. In the manufacturing process for manufacturing a carburized steel part using the steel material as a raw material, for example, a gas carburizing treatment is performed on the steel material, as described below. In the gas carburizing treatment, the steel material is subjected to A c3 Since the steel is heated to a temperature equal to or higher than the transformation point temperature, the microstructure of the steel is transformed to austenite, and the influence of the previous structure is eliminated. Therefore, the microstructure of the steel, which is the raw material for the carburized steel part, is not particularly limited. The steel of this embodiment has the content of each element in the chemical composition within the above-mentioned range, and further satisfies formulas (1) to (3). Therefore, when a carburized steel part is manufactured by carrying out a gas carburizing treatment using the steel of this embodiment as the raw material, the carburized steel part can obtain high bending fatigue strength and surface fatigue strength (pitting characteristics).

[0081] [Use of the steel material according to this embodiment] The steel material of this embodiment is suitable as a material for carburized steel parts manufactured by gas carburizing, particularly for carburized steel parts that require bending fatigue strength and surface fatigue strength (pitting characteristics), such as gears used in mechanical products such as automobiles and construction vehicles.

[0082] [Method of manufacturing steel material according to this embodiment] An example of a method for manufacturing the steel material of this embodiment will be described. The method for manufacturing the steel material described below is one example for manufacturing the steel material of this embodiment. Therefore, the steel material having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing the steel material of this embodiment.

[0083] An example of the method for producing a steel material according to the present embodiment includes a step of preparing a material (a material preparation step) and a step of producing a steel material by hot working the material (a hot working step). Each step will be described below.

[0084] [Material preparation process] In the material preparation step, a material for the steel material of this embodiment is prepared. Specifically, molten steel is produced in which the content of each element in the chemical composition is within the range of this embodiment and satisfies formulas (1) to (3). The refining method is not particularly limited, and a well-known method may be used. For example, molten iron produced by a well-known method is refined in a converter (primary refining). The molten steel tapped from the converter is subjected to well-known secondary refining. In the secondary refining, alloy elements are added to adjust the composition, and molten steel is produced in which the content of each element is within the range of this embodiment and has a chemical composition that satisfies formulas (1) to (3).

[0085] The molten steel produced by the above-mentioned refining method is used to produce a material by a known casting method. For example, an ingot is produced by an ingot casting method using the molten steel. Also, a bloom may be produced by a continuous casting method using the molten steel. By the above-mentioned method, a material (ingot or bloom) is produced.

[0086] [Hot processing process] In the hot working process, hot working is performed on the material (ingot or bloom) prepared in the material preparation process to manufacture the steel material (steel bar) of this embodiment. The hot working method may be hot forging or hot rolling. In the following explanation, the case where the hot working is hot rolling will be explained. In this case, the hot working process includes, for example, a blooming process and a finish rolling process.

[0087] [Bulking rolling process] In the blooming process, the material is hot rolled to produce a billet. Specifically, in the blooming process, the material is hot rolled (blooming) by a blooming mill to produce a billet. If a continuous rolling mill is disposed downstream of the blooming mill, the billet after blooming may be further hot rolled by the continuous rolling mill to produce a smaller billet. The heating temperature in the blooming process may be within a known range. The heating temperature is, for example, 1000 to 1300°C.

[0088] [Finish rolling process] In the finish rolling process, the billet produced in the blooming process is hot-rolled using a continuous rolling mill to produce a steel bar. A known temperature is sufficient for the heating temperature in the finish rolling process. The heating temperature is, for example, 900 to 1250°C. The steel after hot rolling is cooled to room temperature. The cooling method is not particularly limited, but is, for example, natural cooling.

[0089] The steel material of this embodiment is manufactured by the above manufacturing method. Note that the above manufacturing method is one example of a manufacturing method for manufacturing the steel material of this embodiment. Therefore, the steel material of this embodiment may be manufactured by a method other than the above manufacturing method. In other words, the manufacturing method is not limited as long as the content of each element in the chemical composition is within the range of this embodiment and the steel material satisfies formulas (1) to (3).

[0090] In the above-mentioned example of the manufacturing method, the hot working step is carried out after the material preparation step. However, in the manufacturing method of the steel material of the present embodiment, the hot working step does not have to be carried out after the material preparation step. In other words, the steel material of the present embodiment may be a cast material (ingot, bloom, or billet).

[0091] In addition, the steel material after the material preparation process or the steel material after the hot working process may be subjected to a known normalizing treatment and / or a known spheroidizing annealing. In the spheroidizing annealing, for example, the annealing temperature is set to 720 to 780°C, and the holding time at the annealing temperature is set to 3 to 8 hours. Furthermore, the cooling time from the annealing temperature to 600°C is set to 4 hours or more (8 hours or less). Then, the steel material is allowed to cool.

[0092] [Composition of carburized steel parts] The carburized steel part of this embodiment is manufactured by subjecting the steel material of this embodiment described above to gas carburizing treatment (gas carburizing treatment or gas carbonitriding treatment). The carburized steel part is, for example, a machine part used in automobiles, construction vehicles, etc., such as a gear.

[0093] The carburized steel part of this embodiment comprises a hardened layer and a core located inside the hardened layer. The hardened layer is a layer hardened by the penetration of C by gas carburizing. Specifically, when gas carburizing is performed, the hardened layer corresponds to the carburized layer, and when gas carbonitriding is performed, the hardened layer corresponds to the carbonitrided layer. The core is a part located inside the hardened layer, and is an area that is not affected by the penetration and diffusion of C by gas carburizing. It is a technical matter well known to those skilled in the art that the hardened layer and the core can be distinguished by well-known microstructural observation.

[0094] [About the core] The chemical composition of the core of the carburized steel part of this embodiment is the same as that of the steel material of this embodiment described above. Specifically, the chemical composition of the core of the carburized steel part of this embodiment contains, by mass%, C: 0.10-0.35%, Si: 0.45-1.00%, Mn: 0.40-1.30%, P: 0.030% or less, S: 0.001-0.100%, Cr: 1.63-2.10%, Al: 0.010-0.100%, N: 0.0250% or less, and Mo: 0.02-0.60%, with the balance being Fe and impurities, and satisfies formulas (1) to (3). 6.1≦(Mn+3Cr+2Mo) / Si≦12.0 (1) 3.0≦Cr / Mn (2) 24.0≦Mn / S≦60.0 (3) Here, the content in mass % of the corresponding element is substituted for each element symbol in formulas (1) to (3).

[0095] The chemical composition of the core may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of V: ​​0.50% or less, Nb: 0.100% or less, Ti: 0.200% or less, Cu: 0.50% or less, Ni: 0.30% or less, W: 0.50% or less, Co: 0.50% or less, and B: 0.0050% or less.

[0096] The chemical composition of the core portion may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of Ca: 0.0014% or less, Mg: 0.010% or less, and rare earth elements: 0.0100% or less.

[0097] The chemical composition of the core may further contain, in place of a portion of Fe, one or more elements selected from the group consisting of Te: 0.100% or less, Bi: 0.500% or less, Pb: 0.09% or less, Sn: 0.014% or less, and Sb: 0.0018% or less.

[0098] [About the hardened layer] The composition of the hardened layer is as follows: (1) The carbon concentration in the region from the surface to a depth of 50 μm of the carburized steel component is 0.60% or more by mass. (2) The microstructure of the carburized steel part at a depth of 20 μm from the surface is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. Each component will be described below.

[0099] [Surface C concentration] The area from the surface of the carburized steel part to a depth of 50 μm (hereinafter referred to as the surface region) is included in the hardened layer. The C concentration in the surface region is 0.60% or more by mass. The C concentration in the hardened layer is higher than the C concentration in the core. If the C concentration in the surface region is 0.60% or more by mass, the hardness of the hardened layer is sufficiently high. Therefore, the carburized steel part can obtain sufficient surface fatigue strength and sufficient bending fatigue strength.

[0100] The lower limit of the C concentration in the surface region is preferably 0.65%, more preferably 0.70%, and even more preferably 0.75%. The upper limit of the C concentration in the surface region is not particularly limited. The upper limit of the C concentration in the surface region is preferably 1.30%, for example, more preferably 1.20%, and even more preferably 1.10%.

[0101] [Method for measuring surface carbon concentration] The carbon concentration in the surface region can be measured by the following method. Cutting is performed from the surface of the carburized steel part to a depth of 50 μm, and chips from the surface region to a depth of 50 μm are collected. Chemical analysis is performed using the collected chips. Specifically, the well-known high-frequency combustion method (combustion-infrared absorption method) is performed on the collected chips to obtain the carbon concentration. Specifically, the above-mentioned chips are burned by high-frequency induction heating in an oxygen stream, and the generated carbon dioxide and carbon monoxide are detected to determine the carbon concentration (mass %). The obtained carbon concentration (mass %) is defined as the carbon concentration (mass %) in the region from the surface of the carburized steel part to a depth of 50 μm (surface region).

[0102] [Microstructure of the hardened layer] The hardened layer includes a depth of 20 μm from the surface of the carburized steel part. The microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. In other words, when the microstructure is made of martensite and retained austenite, the volume fraction of the retained austenite is 40% or less. It is technically common knowledge that the microstructure in the hardened layer is mainly martensite.

[0103] If the volume fraction of the retained austenite at a depth of 20 μm from the surface of the carburized steel part exceeds 40%, the hardness of the hardened layer is too low. In this case, the bending fatigue strength of the carburized steel part is reduced. If the volume fraction of the retained austenite at a depth of 20 μm from the surface of the carburized steel part is 40% or less, the hardened layer has sufficient hardness. Therefore, the bending fatigue strength of the carburized steel part is increased. The preferred upper limit of the volume fraction of the retained austenite at a depth of 20 μm from the surface of the carburized steel part is 35%, more preferably 30%, and even more preferably 28%. The lower the volume fraction of the retained austenite, the better. However, it is difficult to reduce the retained austenite to 0%, and the manufacturing cost is also high. Therefore, in consideration of industrial production, the preferred lower limit of the retained austenite is more than 0%, and even more preferably 1%.

[0104] [Method for measuring volume fraction of retained austenite] The volume fraction of retained austenite is measured by the following method. A carburized steel component is electrolytically polished to a depth of 20 μm from the surface, and a portion 20 μm deep from the surface is exposed. An X-ray diffraction device is used to irradiate any position on the exposed surface with X-rays to measure the volume fraction (%) of retained austenite. The volume fraction of retained austenite is calculated from the ratio (integral intensity ratio) of the integrated intensity of the (211) bcc diffraction peak obtained by X-ray diffraction to the integrated intensity of the (220) fcc diffraction peak. Specifically, the volume fraction (%) of retained austenite can be calculated from the following formula, where the integrated intensity of (211) bcc (α phase) is Iα and the integrated intensity of (220) fcc (γ phase) is Iγ. Volume fraction of retained austenite = Iγ / (RIα+Iγ) Here, R = 0.36746.

[0105] The carburized steel part having the above configuration has the content of each element in the chemical composition of the core within the above-mentioned range, and satisfies formulas (1) to (3). Furthermore, the C concentration in the region (surface region) from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more, and the microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or martensite and retained austenite, with the volume fraction of retained austenite being 0 to 40%. Therefore, the carburized steel part of this embodiment has high bending fatigue strength and high surface fatigue strength.

[0106] [Manufacturing method for carburized steel parts] An example of a manufacturing method for the carburized steel part of this embodiment will be described. The manufacturing method for the carburized steel part described below is one example for manufacturing the carburized steel part of this embodiment. Therefore, the carburized steel part having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a manufacturing method for the carburized steel part of this embodiment.

[0107] The carburized steel part is subjected to a hot working process or a cold working process, a cutting process, and a heat treatment process. Either the hot working process or the cold working process is performed.

[0108] [Hot processing process] When the hot working step is carried out, hot working is carried out on the steel material of this embodiment. The hot working is, for example, well-known hot forging. The heating temperature in the hot working step is, for example, 1000 to 1300°C. After the hot working, the steel material is naturally cooled (air-cooled).

[0109] [Cold working process] When the cold working step is performed, the steel material of the present embodiment is subjected to a well-known spheroidizing annealing, and then cold working is performed. The conditions of the cold working are not particularly limited.

[0110] [Cutting process] In the cutting process, the steel material after the hot working process is cut to produce an intermediate product of a predetermined shape. By performing cutting, it is possible to give the carburized steel part a precise shape that would be difficult to achieve by the hot working process or cold working process alone.

[0111] [Heat treatment process] The intermediate product after the cutting process is subjected to a heat treatment. Here, "heat treatment" includes a well-known gas carburizing process and a well-known tempering process. The gas carburizing process includes a gas carburizing process and a quenching process. In the gas carburizing process, it is a technical matter well known to those skilled in the art to appropriately adjust well-known conditions to adjust the C concentration and microstructure of the hardened layer of the carburized steel part. Hereinafter, the well-known gas carburizing process will be described as an example of a heat treatment process.

[0112] [Gas carburizing process] The gas carburizing process includes a gas carburizing process and a quenching (quenching) process. The gas carburizing process and the quenching process will be described below.

[0113] [Gas carburizing process] Fig. 1 is a diagram showing an example of a heat pattern in the gas carburizing step S10 and the quenching step S20. The vertical axis of Fig. 1 is the treatment temperature (°C) during the gas carburizing treatment, and the horizontal axis is the time (min). With reference to Fig. 1, the gas carburizing step S10 includes a heating step S0, a carburizing step S1, and a diffusion step S2.

[0114] In the heating step S0, the intermediate product placed in the furnace is heated to a carburizing temperature Tc. The carburizing temperature Tc in the heating step S0 is, for example, 900 to 1100°C.

[0115] In the carburizing step S1, the intermediate product is held for a predetermined time (holding time t1) at the carburizing temperature Tc in an atmosphere of a predetermined carbon potential CP1 to perform carburizing treatment. The carbon potential CP1 in the carburizing step S1 is, for example, 0.6 to 1.3%, and the holding time t1 at the carburizing temperature Tc is, for example, 60 minutes or more.

[0116] In the diffusion step S2, the carburization temperature Tc is held for a predetermined time (holding time t2) in an atmosphere of a predetermined carbon potential CP2. Here, the carbon potential CP2 in the diffusion step S2 is, for example, 0.6 to 1.3%, and the holding time t2 at the carburization temperature Tc is, for example, 30 minutes or more. It is preferable that the carbon potential CP2 in the diffusion step S2 is lower than the carbon potential CP1 in the carburization step S1.

[0117] [Quenching process] The intermediate product after the gas carburizing process S10 is subjected to the quenching process S20. In the quenching process S20, the intermediate product after the gas carburizing process S10 is r3 After being held at a quenching temperature equal to or higher than the quenching temperature Ts, the intermediate product is quenched and quenched. The holding time t3 at the quenching temperature Ts is not particularly limited, but is, for example, 15 to 60 minutes. The quenching temperature Ts is preferably lower than the carburizing temperature Tc. The cooling method in the quenching process is oil cooling or water cooling. Specifically, the intermediate product held at the quenching temperature is immersed in a cooling bath containing oil or water as a cooling medium to be quenched.

[0118] [Tempering process] The intermediate product after the quenching process is subjected to a known tempering process. The tempering temperature is, for example, 100 to 200° C. The holding time at the tempering temperature is, for example, 90 to 150 minutes.

[0119] [Other processes] The method for manufacturing the carburized steel part of this embodiment may further include a shot peening step and a finish grinding step, which are optional steps.

[0120] [Shot peening process] The shot peening process is an optional process and does not have to be performed. If performed, the shot peening process is performed on the intermediate product after the heat treatment process. By performing the shot peening process, the retained austenite in the hardened layer of the carburized steel part undergoes processing-induced transformation to martensite. As a result, the volume fraction of the retained austenite in the hardened layer decreases. For example, the shot peening process preferably uses a cut wire or shot grains with a diameter of 1.0 mm or less, has an arc height of 0.3 mmA or more, and has a coverage of 300% or more.

[0121] [Finishing grinding process] The finish grinding process is an optional process and does not have to be performed. If performed, the finish grinding process is performed on the intermediate product after the heat treatment process or the shot peening process to adjust the surface properties.

[0122] The carburized steel part of this embodiment can be manufactured by the above manufacturing process. The above manufacturing method is one example of a manufacturing method for manufacturing the carburized steel part of this embodiment. Therefore, the carburized steel part of this embodiment may be manufactured by a method other than the above manufacturing method. In other words, the manufacturing method of the carburized steel part is not particularly limited as long as the content of each element in the chemical composition of the core of the carburized steel part is within the range of this embodiment and satisfies formulas (1) to (3), the C concentration in the region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more, the microstructure at a depth of 20 μm from the surface of the carburized steel part consists of martensite or consists of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. EXAMPLES

[0123] The effects of the steel material and carburized steel part of this embodiment will be explained in more detail below with reference to examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effects of the steel material and carburized steel part of this embodiment. Therefore, the steel material and carburized steel part of this embodiment are not limited to this one example of conditions.

[0124] [Steel manufacturing] Molten steel having the chemical composition shown in Table 1 was produced.

[0125] [Table 1]

[0126] Ingots were produced by the ingot casting method using the molten steel in Table 1. The cross section perpendicular to the longitudinal direction of the ingot was a rectangle of 180 mm x 180 mm. The produced ingot was allowed to cool to room temperature.

[0127] The ingot was heated at 1200°C for 2 hours. The heated ingot was subjected to hot working (hot forging) to produce steel material (steel bar) having a diameter of 40 mm and a length of 1000 mm. The hot worked steel material was allowed to cool to room temperature. The steel material after cooling was subjected to normalizing treatment. The treatment temperature in the normalizing treatment was 925°C, and the holding time at the treatment temperature was 90 minutes. After the holding time had elapsed, the steel material was allowed to cool. The cooling rate of the steel material during cooling was 0.3 to 0.9°C / sec. Through the above steps, the steel material (steel bar) of each test number was produced.

[0128] The steel material with test number 37 had a chemical composition equivalent to SCr420 as specified in JIS G 4805 (2019). The steel material with test number 37 was designated as the "reference steel material."

[0129] [Evaluation test] [Manufacturing of carburized steel part test pieces] The steel materials produced for each test number were used to prepare the following three types of carburized steel part test pieces for each test number. (1) Small roller test piece Figure 2 shows a side view of the small roller test piece produced in this example. The numbers in Figure 2 indicate dimensions (unit: mm). "φ" in Figure 2 means diameter. The inverted triangle symbol in Figure 2 means the "finishing symbol" indicating the surface roughness described in Table 1 of JIS B 0601 (1982). The "G" attached to the finishing symbol means the abbreviation of the processing method indicating the grinding specified in JIS B 0122 (1978). The small roller test piece is a test piece for measuring surface fatigue strength. Multiple small roller test pieces were prepared for each test number. (2) Rotating bending fatigue test piece Figure 3 shows a side view of the rotating bending fatigue test piece produced in this example. The numbers in Figure 3 indicate dimensions (unit: mm). "φ" in Figure 3 means diameter. "R" in Figure 3 means radius of curvature. The rotating bending fatigue test piece is a test piece for measuring rotating bending fatigue strength. (3) Test pieces for hardened layer investigation Two test pieces were prepared for each test number to investigate the hardened layer. The test pieces were cylindrical, measuring 26 mm in diameter and 100 mm in length.

[0130] Test pieces for each carburized steel component were prepared in the following manner.

[0131] [Small roller test piece] The steel material of each test number was machined to produce a rough test piece having the rough shape of the small roller test piece. Gas carburizing treatment (gas carburizing quenching and tempering) was performed on the rough test piece. Specifically, the test piece was held at 930°C for 180 minutes in an atmosphere with a carbon potential CP of 1.0% (carburizing process). Then, the carbon potential CP was set to 0.8% and held at 930°C for 120 minutes (diffusion process). Then, the temperature was lowered to 870°C, held at 870°C for 30 minutes, and then oil-cooled in oil at 60°C (quenching process). Tempering treatment was performed on the rough test piece after oil cooling. The tempering temperature was 180°C, and the holding time at the tempering temperature was 120 minutes. Then, grinding was performed on the cylindrical part in the center of the rough test piece to finish it into a cylindrical part with a diameter of 26 mm as shown in Figure 2. At this time, the surface of the cylindrical portion having a diameter of 26 mm was finished so that the arithmetic mean roughness Ra was 0.6 to 0.8 μm and the maximum height Rz was 2.0 to 4.0 μm in accordance with JIS B 0601 (2001). The grinding depth was about 10 μm.

[0132] Furthermore, shot peening was performed on the crude test pieces of some of the test numbers (indicated as "Yes" in the "Shot Peening" column in Table 2). For the shot peening, a commercially available round cut wire with a diameter of 0.6 mm was used as the blast material. Furthermore, the arc height was 0.4 mmA, and the coverage was 300%. Shot peening was performed on the outer circumferential surface of the cylindrical part with a diameter of 26 mm shown in Figure 2. Shot peening was not performed on the crude test pieces of the remaining test numbers (indicated as "No" in the "Shot Peening" column in Table 2). Small roller test pieces were produced by the above manufacturing process.

[0133] [Rotating bending fatigue test piece] The steel material of each test number was machined to produce a rough test piece for the rotating bending fatigue test. The rough test pieces were subjected to gas carburizing treatment (gas carburizing quenching and tempering). Specifically, the test pieces were held at 930°C for 180 minutes in an atmosphere with a carbon potential CP of 1.0% (carburizing process). Then, the carbon potential CP was set to 0.8% and held at 930°C for 120 minutes (diffusion process). Then, the temperature was lowered to 870°C, held at 870°C for 30 minutes, and then oil-cooled in oil at 60°C (quenching process). The rough test pieces after oil cooling were subjected to tempering treatment. The tempering temperature was 180°C, and the holding time at the tempering temperature was 120 minutes. For some test numbers, the rough test pieces after tempering were subjected to shot peening treatment (indicated as "Yes" in the "Shot Peening" column in Table 2). In the shot peening treatment, a commercially available round cut wire with a diameter of 0.6 mm was used as the shot material. Furthermore, the arc height was set to 0.4 mmA, and the coverage was set to 300%. The shot peening treatment was performed on the notch of the rotary bending test piece. The shot peening treatment was not performed on the rough test pieces with the remaining test numbers ("None" is written in the "Shot Peening" column in Table 2).

[0134] After shot peening or tempering, the surface of the rough test piece was machined to prepare a rotating bending fatigue test piece with the dimensions shown in Fig. 3. Note that no machining was performed to adjust the surface properties of the notch formed in the center of the longitudinal direction of the rotating bending fatigue test piece. The rotating bending fatigue test piece was prepared by the above manufacturing process.

[0135] [Test piece for hardened layer investigation] The steel material of each test number was machined to prepare two cylindrical rough test pieces with a diameter of 26 mm and a length of 100 mm. Gas carburizing treatment (gas carburizing quenching and tempering) was performed on the rough test pieces. Specifically, the test pieces were held at 930°C for 180 minutes in an atmosphere with a carbon potential CP of 1.0% (carburizing process). Then, the carbon potential CP was set to 0.8% and held at 930°C for 120 minutes (diffusion process). Then, the temperature was lowered to 870°C, and after holding at 870°C for 30 minutes, the rough test pieces were oil-cooled with oil at 60°C (quenching process). Tempering treatment was performed on the rough test pieces after oil cooling. The tempering temperature was 180°C, and the holding time at the tempering temperature was 120 minutes. Then, similar to the small roller test pieces, grinding was performed on the outer peripheral surface of the rough test pieces to finish the outer peripheral surface. At this time, the outer peripheral surface of the rough test piece having a diameter of 26 mm was finished so that the arithmetic mean roughness Ra was 0.6 to 0.8 μm and the maximum height Rz was 2.0 to 4.0 μm according to JIS B 0601 (2001). The grinding depth was about 10 μm.

[0136] Furthermore, shot peening was performed on the rough test pieces of some of the test numbers (indicated as "Yes" in the "Shot Peening" column in Table 2). In the shot peening, a commercially available round cut wire with a diameter of 0.6 mm was used as the blast material. Furthermore, the arc height was set to 0.4 mmA, and the coverage was set to 300%. The shot peening was performed on the outer circumferential surface of the rough test pieces. No shot peening was performed on the rough test pieces of the remaining test numbers (indicated as "No" in the "Shot Peening" column in Table 2). Test pieces for investigating the hardened layer were produced by the above manufacturing process.

[0137] [Manufacturing of large roller test pieces for twin-roller fatigue testing] Large roller test pieces used in twin-cylinder rolling fatigue tests to measure surface fatigue strength were manufactured in the following manner. Rough test pieces for large roller test pieces with the shape shown in Figure 4 were cut out from a cylindrical material with a diameter of 140 mm and a chemical composition equivalent to SUJ2 as specified in JIS G 4805 (2008). The numbers in Figure 4 indicate dimensions (unit: mm). The inverted triangle symbol in Figure 4 indicates the "finishing symbol" indicating the surface roughness described in Table 1 of JIS B 0601 (1982). The "G" attached to the finishing symbol indicates the abbreviation for the processing method indicating grinding as specified in JIS B 0122 (1978).

[0138] The cut rough test pieces were quenched. The quenching temperature was 870°C, and the holding time at the quenching temperature was 90 minutes. After the holding time had elapsed, the rough test pieces were quenched in oil at 60°C. The outer peripheral surface of the quenched rough test pieces was finished by cutting. The outer peripheral surface was finished so that the arithmetic mean roughness Ra was 0.6 to 0.8 μm and the maximum height Rz was 2.0 to 4.0 μm. Large roller test pieces were produced by the above manufacturing process.

[0139] [C concentration measurement test of hardened layer of carburized steel part specimen] Using the test pieces for hardened layer investigation of each test number, the carbon concentration in the region from the surface to a depth of 50 μm was measured by the following method. The test pieces for hardened layer investigation were turned to a depth of 50 μm from the surface, and chips were collected. Chemical analysis was performed using the collected chips. Specifically, the collected chips were dissolved in acid to obtain a solution. The well-known high-frequency combustion method (combustion-infrared absorption method) was performed on the obtained solution to obtain the carbon concentration. Specifically, the above-mentioned solution was burned by high-frequency induction heating in an oxygen stream, and the generated carbon dioxide was detected to obtain the carbon concentration (mass%). The obtained carbon concentration (mass%) was defined as the carbon concentration (mass%) in the region from the surface of the carburized steel part to a depth of 50 μm (surface region).

[0140] [Measurement test of retained austenite volume fraction in the hardened layer of carburized steel part specimens] Using the test pieces for hardened layer investigation of each test number, the volume fraction of retained austenite at a depth of 20 μm from the surface of the carburized steel part was determined by the following method. The carburized steel part was electrolytically polished to a depth of 20 μm from the surface, and the 20 μm depth from the surface was exposed. Using an X-ray diffractometer, an arbitrary position on the exposed surface was irradiated with X-rays to measure the volume fraction (%) of retained austenite. The volume fraction of retained austenite was calculated from the ratio (integral intensity ratio) of the integrated intensity of the diffraction peak of (211)bcc obtained by X-ray diffraction to the integrated intensity of the diffraction peak of (220)fcc. Specifically, the volume fraction (%) of retained austenite was calculated from the following formula, where the integrated intensity of (211)bcc (α phase) is Iα and the integrated intensity of (220)fcc (γ phase) is Iγ. Volume fraction of retained austenite = Iγ / (RIα+Iγ) Here, R = 0.36746.

[0141] [Surface fatigue strength measurement test (two-cylinder rolling fatigue test)] A two-cylinder rolling fatigue test was carried out using the small roller test piece and the large roller test piece, and the surface fatigue strength was determined as follows. A Komatsu Engineering RP201 test machine was used. As shown in FIG. 5, the small roller test piece 10 was rolled while being in contact with the cylindrical portion having a diameter of 26 mm and the central position of the outer peripheral surface of the large roller test piece 20 (the outer peripheral portion having a diameter of 130 mm). The contact pressure was 3.4 GPa in Hertzian pressure. The rotation speed of the small roller test piece was 1500 rpm. The peripheral speed of the small roller test piece was 123 m / min, and the peripheral speed of the large roller test piece was 172 m / min. During the test, lubricating oil was supplied to the contact portion between the small roller test piece and the large roller test piece. The lubricating oil was automatic transmission oil, the oil temperature was 100° C., and the oil amount was 1.0 L / min. The number of rolling repetitions (number of cycles) until fatigue peeling (pitting damage) occurred at the contact portion of the cylindrical portion of the small roller test piece was measured. The test was performed on three small roller test pieces, and the arithmetic mean value of the number of rolling cycles was taken as the average number of rolling cycles for that test number. If the average number of rolling cycles was 1.3 times or more the average number of rolling cycles for the reference steel material, test number 37, it was judged to have excellent surface fatigue strength (marked "○" in the "Contact fatigue strength" column in Table 2). On the other hand, if the average number of rolling cycles was less than 1.3 times the average number of rolling cycles for the reference steel material, test number 37, it was judged to have low surface fatigue strength (marked "X" in the "Contact fatigue strength" column in Table 2).

[0142] [Rotating bending strength measurement test (rotating bending fatigue test)] Rotating bending fatigue tests were conducted using rotating bending fatigue test pieces in accordance with the "Rotating bending fatigue test method for metallic materials" specified in JIS Z 2274 (1978). Rotating bending fatigue tests were conducted under various conditions until the rotating bending fatigue test pieces broke, with a repetition rate of 2 × 10 7 The bending fatigue strength (MPa) after 1000 cycles was calculated. If the bending fatigue strength obtained was 1.15 times or more that of the reference steel material, test number 37, it was determined that the bending fatigue strength was excellent (marked "○" in the "Bending fatigue strength" column in Table 2). On the other hand, if the bending fatigue strength obtained was less than 1.15 times that of the reference steel material, test number 37, it was determined that the bending fatigue strength was low (marked "×" in the "Bending fatigue strength" column in Table 2).

[0143] [Evaluation Results] The test results are shown in Table 2.

[0144] [Table 2]

[0145] Referring to Table 2, the contents of each element in the chemical composition of the steel materials of test numbers 1 to 22 were appropriate, and furthermore, F1 to F3 satisfied formulas (1) to (3). Therefore, in the carburized steel parts manufactured by gas carburizing, the C concentration in the region from the surface of the carburized steel part to a depth of 50 μm was 0.60% by mass or more, and the microstructure at a depth of 20 μm from the surface of the carburized steel part was composed of martensite and retained austenite, with the volume fraction of retained austenite being 40% or less. As a result, excellent bending fatigue strength and excellent surface fatigue strength were obtained.

[0146] On the other hand, in test number 23, the C content was too low, and therefore the contact fatigue strength was low.

[0147] In test number 24, the Si content was too high. Therefore, the C content in the surface layer was too low, and the contact fatigue strength was low.

[0148] In test number 25, the Si content was too low, which resulted in low contact fatigue strength.

[0149] In test number 26, the Mn content was too high. As a result, the bending fatigue strength was low. In addition, because the Mn content was too high, the volume fraction of retained austenite exceeded 40% in the microstructure at a depth of 20 μm from the surface of the carburized steel part.

[0150] In test number 27, the Mn content was too low, which resulted in low bending fatigue strength and surface fatigue strength.

[0151] In test number 28, the P content was too high, which resulted in low bending fatigue strength.

[0152] In test number 29, the S content was too high, which resulted in low bending fatigue strength.

[0153] In test number 30, the Cr content was too high, which resulted in low bending fatigue strength.

[0154] In test number 31, the Cr content was too low, which resulted in low contact fatigue strength.

[0155] In test number 32, the contents of each element in the chemical composition of the steel were appropriate, but F3 was below the lower limit of formula (3), and therefore the bending fatigue strength was low.

[0156] In test number 33, the N content was too high, which resulted in low surface fatigue strength and bending fatigue strength.

[0157] In test number 34, the content of each element in the chemical composition of the steel was appropriate, but F1 exceeded the upper limit of formula (1). As a result, the bending fatigue strength was low.

[0158] In test number 35, the content of each element in the chemical composition of the steel was appropriate, but F1 was below the lower limit of formula (1). As a result, the contact fatigue strength was low.

[0159] In test number 36, the content of each element in the chemical composition of the steel was appropriate, but F2 was below the lower limit of formula (1). As a result, the bending fatigue strength was low.

[0160] In test number 38, the content of each element in the chemical composition of the steel was appropriate, but F3 exceeded the upper limit of formula (3). As a result, the bending fatigue strength was low.

[0161] In test number 39, the contents of each element in the chemical composition of the steel were appropriate, but F3 was below the lower limit of formula (3). As a result, the bending fatigue strength was low.

[0162] In test number 40, the content of each element in the chemical composition of the steel was appropriate, but F1 was below the lower limit of formula (1). As a result, the contact fatigue strength was low.

[0163] In test number 41, the content of each element in the chemical composition of the steel was appropriate, but F1 exceeded the upper limit of formula (1). As a result, the bending fatigue strength was low.

[0164] In test number 42, the contents of each element in the chemical composition of the steel were appropriate, but F2 was below the lower limit of formula (2). As a result, the bending fatigue strength was low.

[0165] The above describes the embodiments of the present invention. However, the above-described embodiments are merely examples for carrying out the present invention. Therefore, the present invention is not limited to the above-described embodiments, and the above-described embodiments can be appropriately modified and carried out without departing from the spirit of the present invention.

Claims

1. Chemical composition in mass percent: C: 0.10-0.35%, Si: 0.45-1.00%, Mn: 0.40 to 1.30%, P: 0.030% or less, S: 0.001-0.100%, Cr: 1.63-2.10%, Al: 0.010-0.100%, N: 0.0250% or less, Mo: 0.02-0.60%, V: 0-0.50%, Nb: 0 to 0.100%, Ti: 0-0.200%, Cu: 0 to 0.50%, Ni: 0 to 0.30%, W: 0-0.50%, Co: 0 to 0.50%, B: 0 to 0.0050%, Ca: 0-0.0014%, Mg: 0 to 0.010%, Rare earth elements: 0 to 0.0100%, Te: 0 to 0.100%, Bi: 0-0.500%, Pb: 0 to 0.09%, Sn: 0 to 0.014%, and Sb: 0 to 0.0018%, The balance is Fe and impurities, and satisfies formulas (1) to (3). Steel material. 7.3≦(Mn+3Cr+2Mo) / Si≦11.9 (1) 3.0≦Cr / Mn (2) 26.7≦Mn / S≦52.0 (3) Here, the content of the corresponding element in mass % is substituted for each element symbol in formulas (1) to (3).

2. The steel material according to claim 1, The chemical composition is, in place of a part of Fe, V: 0.01-0.50%, Nb: 0.001 to 0.100%, Ti: 0.001 to 0.200%, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.30%, W: 0.01-0.50%, Co: 0.01 to 0.50%, and B: 0.0001 to 0.0050%, Contains one or more selected from the group consisting of Steel material.

3. The steel material according to claim 1 or 2, The chemical composition is, in place of a part of Fe, Ca: 0.0001-0.0014%, Mg: 0.001 to 0.010%, and Rare earth elements: 0.0001 to 0.0100%, Contains one or more selected from the group consisting of Steel material.

4. The steel material according to any one of claims 1 to 3, The chemical composition is, in place of a part of Fe, Te: 0.001 to 0.100%, Bi: 0.001-0.500%, Pb: 0.01-0.09%, Sn: 0.001 to 0.014%, and Sb: 0.0001 to 0.0018%, Contains one or more selected from the group consisting of Steel material.

5. A carburized steel part, A hardened layer; A core portion is provided inside the hardened layer, The chemical composition of the core is, in mass%, C: 0.10-0.35%, Si: 0.45-1.00%, Mn: 0.40 to 1.30%, P: 0.030% or less, S: 0.001-0.100%, Cr: 1.63-2.10%, Al: 0.010-0.100%, N: 0.0250% or less, Mo: 0.02-0.60%, V: 0 to 0.50%, Nb: 0 to 0.100%, Ti: 0-0.200%, Cu: 0 to 0.50%, Ni: 0 to 0.30%, W: 0-0.50%, Co: 0 to 0.50%, B: 0 to 0.0050%, Ca: 0-0.0014%, Mg: 0 to 0.010%, Rare earth elements: 0 to 0.0100%, Te: 0 to 0.100%, Bi: 0-0.500%, Pb: 0 to 0.09%, Sn: 0 to 0.014%, and Sb: 0 to 0.0018%, and the balance being Fe and impurities, and satisfying formulas (1) to (3), The carbon concentration in a region from the surface of the carburized steel part to a depth of 50 μm is 0.60% or more by mass%, The microstructure at a depth of 20 μm from the surface of the carburized steel part is made of martensite or made of martensite and retained austenite, and the volume fraction of the retained austenite is 0 to 40%. Carburized steel parts. 7.3≦(Mn+3Cr+2Mo) / Si≦11.9 (1) 3.0≦Cr / Mn (2) 26.7≦Mn / S≦52.0 (3)

6. 6. A carburized steel component according to claim 5, The chemical composition of the core portion is, in place of a part of Fe, V: 0.01-0.50%, Nb: 0.001 to 0.100%, Ti: 0.001 to 0.200%, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.30%, W: 0.01-0.50%, Co: 0.01 to 0.50%, and B: 0.0001 to 0.0050%, Contains one or more selected from the group consisting of Carburized steel parts.

7. A carburized steel part according to claim 5 or claim 6, The chemical composition of the core portion is, in place of a part of Fe, Ca: 0.0001-0.0014%, Mg: 0.001 to 0.010%, and Rare earth elements: 0.0001 to 0.0100%, Contains one or more selected from the group consisting of Carburized steel parts.

8. A carburized steel part according to any one of claims 5 to 7, The chemical composition of the core portion is, in place of a part of Fe, Te: 0.001 to 0.100%, Bi: 0.001-0.500%, Pb: 0.01-0.09%, Sn: 0.001 to 0.014%, and Sb: 0.0001 to 0.0018%, Contains one or more selected from the group consisting of Carburized steel parts.

Citation Information

Patent Citations

  • Production of parts for machine structure

    JP1996120438A

  • Carbonitrided component made of steel

    JP2010070827A

  • Steel for gear excellent in resistance to exfoliation, and gear

    JP2010185123A

  • Carburizing steel

    JP2015134945A

  • Steel component for high strength high toughness machine structure excellent in pitching resistance and abrasion resistance and manufacturing method therefor

    JP2016050350A